If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-5y+10-y=-2)
We move all terms to the left:
(-5y+10-y-(-2))=0
We calculate terms in parentheses: +(-5y+10-y-(-2)), so:We get rid of parentheses
-5y+10-y-(-2)
determiningTheFunctionDomain -5y-y+10-(-2)
We add all the numbers together, and all the variables
-6y+12
Back to the equation:
+(-6y+12)
-6y+12=0
We move all terms containing y to the left, all other terms to the right
-6y=-12
y=-12/-6
y=+2
| 4x+10=−90 | | 215=10x+5 | | 2q^2+10q+3300=0 | | (9x-14-8x=-8) | | 5^2x^-3=25 | | -4(x+1)2-10=-10 | | (5y+29+3y=-20) | | P=2q^2+10q+3300 | | 2(x-4)2+6=78 | | (3y+32-y=18) | | x+3x+(6+x)=149 | | (4y+14-2y=4) | | (44=6x-1+9x) | | (-12y+8y-21=-5) | | .045/x=2.05 | | X²+5x-2=0 | | 9n+46=12n-51 | | 7+4x+5x=9x+7= | | (5x+6)+(3x-2)=180 | | r-26=15 | | (4-3x-7x=-8) | | y=-3/2(6/1)+6 | | .6x+8=2(3x+4) | | (2x+4-6x=24,5) | | 2/11+16=4+6/11x | | 30=y/26 | | 30=26-g | | 80.26-87c=c | | 5(1−x)2−6(x2−3x−7)=x(x−3)−2x(x+5)−2 | | (4-3x-7x=-8,7) | | -17=3n-5+7n | | y/2+47=7 |